Impact De L’exploitation Artisanale De La Sabliere De Toutsang Sur La Structure Des Communautes De Macroinvertebres Du Cours D’eau Doulahang A Dschang (Ouest Cameroun) - Norbert, Ngameni Tchamadeu; Fai, Asanga Patricia; Mbida, Mpoame; Brice, Kenko NKontcheu Daniel (European Scientific Journal, ESJ, 2017)
The impact of wastewaters from the Toutsang sandpit (Dschang), both on water parameters and on benthic macro-invertebrate community structure of the Doulahang stream was studied from March 2015 to February 2016 on a monthly basis in three sampling stations named TS1, TS2 and TS3. The physico-chemical analysis were carried out according to standard protocols while the benthic macro-fauna was harvested using a haze net of 30 cm side and 400 μm mesh size. The analysis of physico-chemical parameters revealed that the introduction of wastewater from the sandpit at the TS2 station led to an increase of the temperature, conductivity, total dissolved solids, salinity, suspended matter, turbidity and colour. The wildlife inventory identified 63 taxa divided into 4 phyla, 6 classes, 13 orders and 31 families. The lowest values of the taxonomic richness (18 taxa, against 46 taxa and 47 taxa respectively to stations TS1 and TS3), the Shannon diversity index (2.48 bits / ind.) and the Pielou's evenness (0.62) were observed at station TS2 which received wastewaters from the sandpit. Similarly, the low values of the richness and abundance of the pollutionsensitive groups (Ephemeroptera-Trichoptera-Odonata) were recorded in this station. Significant negative correlations were found between some metrics (total taxonomic richness, taxonomic richness of the Diptera, Richness of Ephemeroptera-Trichoptera-Odonata, Taxonomic richness of insects, Relative abundance of Ephemeroptera-Trichoptera-Odonata, Shannon Weaver diversity index, Pielou's evenness) descriptors of the structure of benthic macro-fauna communities and physico-chemical parameters indicative of physical pollution such as turbidity, suspended matter and colour.